2021
DOI: 10.1093/hmg/ddab140
|View full text |Cite
|
Sign up to set email alerts
|

Human photoreceptor cells from different macular subregions have distinct transcriptional profiles

Abstract: The human neural retina is a light sensitive tissue with remarkable spatial and cellular organization. Compared to the periphery, the central retina contains more densely packed cone photoreceptor cells with unique morphologies and synaptic wiring. Some regions of the central retina exhibit selective degeneration or preservation in response to retinal disease and the basis for this variation is unknown. In this study, we used both bulk and single-cell RNA sequencing to compare gene expression within concentric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…6 ) ( 46 ), we calculated the expression level in each choroidal cell population (using data from the current study), each retinal cell population (using data from Voigt et al. ( 65 )), and in the RPE (using data from Voigt et al. (19 )).…”
Section: Methodsmentioning
confidence: 99%
“…6 ) ( 46 ), we calculated the expression level in each choroidal cell population (using data from the current study), each retinal cell population (using data from Voigt et al. ( 65 )), and in the RPE (using data from Voigt et al. (19 )).…”
Section: Methodsmentioning
confidence: 99%
“…Differences in the function, distribution and morphology of retinal cells between fovea and peripheral retina are associated with marked differences in gene expression (Peng et al, 2019;Voigt et al, 2019bVoigt et al, , 2021Yan et al, 2020). Using unstructured statistical methods that assessed how close transcription profiles from a large number of cells are, foveal cones were found to form clusters that were distinct from their peripheral counterparts (Voigt et al, 2019b).…”
Section: Retinal Neuronsmentioning
confidence: 99%
“…Patterns of retinal atrophy in inherited retinal disease can be traced to specific cell types. We and others (55) have previously demonstrated that different retinal and choroidal cell types express unique gene expression profiles, and such profiles can vary regionally even within a single cell type. The m.3243A>G mutation causes a characteristic macular atrophy (Figure 1A).…”
Section: Discussionmentioning
confidence: 86%